TA-1 Impact of tea and coffee consumption on stroke and Parkinson disease: A Sri Lankan perspective - Attanayake, M.K.D.K.; Amaratunga, D.; Gamage, R.; Ragunathan, M.K.; Fernando, H.; Liyanage, J.; Kulthunga, A.; Gunasekara, H.; Dissanayake, Lakshman; Suriyakumara, S.V.T.; Udawatte, N. S.; De Silva, K.R.D. (Federation of Asian-Oceanian Neuroscience Societies, 2015)
Introduction: Tea & coffee consumption could potentially reduce the risk of Stroke & Parkinson Disease (PD) due to their antioxidant properties. However cigarette smoking is lead to oxidative stress that may alter the cellular antioxidant defense system. Method: Study population of 1415 individuals; Stroke:n=772; [Stroke in young patients «45 yrs) accounted for 16% (124/772), median age of onset 38Yrs; male 12% (94/124) 37Yrs, female 4% (30/124) 38Yrs; sex ratio of 3.31: 1. Stroke with age~46; male 56% (402/648) & female 34% (246/648) sex ratio of 1.63: 1], PD: n=143; [Male 61% (87/143), female 39%(56/143), median age of onset 57Yrs] & age matched controls: n=500. Tea, coffee & cigarette consumption were assessed by a stranded questionnaire. Results: Stroke with tea consumptlon..aacups/day 63% (490), 2cups/day 23% 434 (177), 1cup/day 9% (70), median age of onset: 62, 59 & 56Yrs respectively. Stroke with coffee drinkers 36% (278), non-drinkers 64% (494), median age of onset: 61 & 62Yrs respectively. Stroke with smoking 27% (211), non- smoking 37% (288), median age of onset: 60 & 61Yrs respectively. PO with tea consumption: ~3cups/day 51 % (73), 2cups/day 36% (51), 1cup/day 12% (17), median age of onset was 57Yrs in all categories. PO with coffee drinkers 41 % (58), non-drinkers 55% (80), median age of onset: 56 & 57Yrs respectively. PO with smoking 29% (42), non- smoking 71 % (101) median age of onset: 57Yrs in both categories. Conclusion: Results suggestive of regular consumption of Ceylon tea is associated with a decreased risk of early onset of Stroke & PO, where coffee consumption plays a protective role towards early onset of PO, study lay steppingstone on developing neuroprotective nutraceuticals based on unique regional natural products.
Keywords: stroke PD tea coffee smoking